2017
DOI: 10.1096/fj.201601063r
|View full text |Cite
|
Sign up to set email alerts
|

Maternal smoke exposure decreases mesenchymal proliferation and modulates Rho‐GTPase‐dependent actin cytoskeletal signaling in fetal lungs

Abstract: The present study tested the hypothesis that maternal smoke exposure results in fetal lung growth retardation due to dysregulation in various signaling pathways, including the Wnt (wingless-related integration site)/β-catenin pathway. Pregnant female C57BL/6J mice were exposed to cigarette smoke (100-150 mg/m) or room air, and offspring were humanely killed on 12.5, 14.5, 16.5, and 18.5 d (dpc). We assessed lung stereology with Cavalieri estimation; apoptosis with proliferating cell nuclear antigen, TUNEL, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 63 publications
(88 reference statements)
0
6
0
Order By: Relevance
“…Adverse effects on lung function (Drummond et al, 2017) and morphology (Noel et al, 2017) have been shown and synergistic effects between pre- and postnatal exposure have been identified. A recent study provided first insights into CS-related transcriptional alterations in the fetal lung (Unachukwu et al, 2017). Regarding ambient air pollution, however, we yet remain the first to provide evidence of an effect of prenatal and early-life postnatal exposure to particulate matter on lung development.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse effects on lung function (Drummond et al, 2017) and morphology (Noel et al, 2017) have been shown and synergistic effects between pre- and postnatal exposure have been identified. A recent study provided first insights into CS-related transcriptional alterations in the fetal lung (Unachukwu et al, 2017). Regarding ambient air pollution, however, we yet remain the first to provide evidence of an effect of prenatal and early-life postnatal exposure to particulate matter on lung development.…”
Section: Discussionmentioning
confidence: 99%
“…The Wnt signaling is essential for lung organogenesis, as it is active throughout the development of the fetal lung. In the embryonic lung, it regulates cellular fate, proliferation and differentiation, stem cell maintenance, and lung branching morphogenesis (41,104). Numerous in vitro and in vivo studies using gene knockdown approaches as well as knockout and transgenic mouse models enabled isolation and identification of the roles and functions of specific Wnt-related genes in lung morphogenesis (41).…”
Section: L716mentioning
confidence: 99%
“…GO-term analysis of downregulated protein-coding genes was enriched in the regulation of rho protein signal transduction ( SFig. 2 ), previously reported to be dysregulated by smoke exposure (34, 35). To determine whether CS exposure effects extend beyond changes at the level of transcription, we next measured cytokine and chemokine protein production changes secreted from CS-exposed BMDMs by ELISA, finding that Il9, Il16, Gcsf, and Vegf were all significantly downregulated by CS ( Fig.1F-I ).…”
Section: Resultsmentioning
confidence: 99%